ChemInform Abstract: Supramolecular Catalysis in the Synthesis of Substituted 1H‐Tetrazoles from Isonitriles by a Self‐Assembled Hexameric Capsule. Issue 29 (July 2015) - Giust, Sonia; La Sorella, Giorgio; Sperni, Laura; Fabris, Fabrizio; Strukul, Giorgio; Scarso, Alessandro
Abstract The synthesis of substituted 1H‐tetrazoles from aliphatic or aromatic isonitriles and trimethylsilyl azide can be efficiently promoted by the hexameric capsule of resorcin[4]arene as a supramolecular self‐assembled catalyst.